CFD Calculation Of Impinging Confined Gas Jet Flamesfires - Anuar, Syed Muhammad Syimir Syed Mohamed (Universiti Sains Malaysia, 2017)
The Piper Alpha disaster incident occurred in 1998 clearly demonstrated the potential risk that could result in escalation of hazards when jet fires impinge on structures. Impinging jets flow has been widely used in many industrial applications as a technique to enhance heat and mass transfer in heating, cooling, and drying cases. Jet fires method usually occurs in house process equipment inside the offshore facilities where the probability of having flame impinging on vessels, pipework, and structural support is high. The nature of jet fires that propagate under flame-turbulence interaction flow and high pressure could cause failures to all equipment. This leads to the interest in studying jet fire characteristic in predicting the potential risk to structures and personnel of accidental ignition releases. This research focused on the study of combustion characteristics through the effect of impinging jet flames in a confined area. In this study, a numerical investigation on the heat transfer rate over the flame temperature at combustor wall is made. SolidWorks software is used to model the physical problem while ANSYS Fluent software is used to simulate flow behavior of impinging jet fire in a confined area. Three factors have been examined, i.e., the thickness of the combustor wall, size of nozzle, and radiation effect. The results show that temperature is the highest at the combustor wall when the wall thickness is 0.3 mm and the size of nozzle is 0.2 mm in diameter, which both at 380.28 K. The results also indicate that if the radiation effect is taken into account, a higher temperature reading is expected at the combustor wall. The results also show that high heat transfer rate occurs for thin wall, big nozzle size in diameter, and without consideration of radiation.